miR-29c Inhibits Renal Interstitial Fibrotic Proliferative Properties through PI3K-AKT Pathway - Weifeng Feng; Huijun Xie; Jiong Li; Xianxin Yan; Shiping Zhu; Shengyun Sun (Applied Bionics and Biomechanics)
Renal fibrosis, in particular tubulointerstitial fibrosis, which is characterized by an increased extracellular matrix (ECM) formation and development in the interstitium, is the common end pathway for nearly all progressive kidney disorders. One of the sources for this matrix is the epithelial to mesenchymal transition (EMT) from the tabular epithelium. The driving force behind it is some profibrotic growth factors such as transforming growth factor-β (TGF-β) which is responsible for the formation of collagen in renal fibrosis. miR-29c, which is an antifibrotic microRNA, downregulates renal interstitial fibrosis by downregulating the TGF-β and collagen. However, it is not known whether miR-29c mediates the TGF-β1-driven PI3K-Akt pathway and Col-1 triggering within NRK-52E cultures. The main objective of this investigation was to examine the influence of miR-29c on the downregulation of the TGF-β1-driven PI3K-Akt pathway and Col-1 triggering in NRK-52E cultures. This study revealed that miR-29c inhibited TGF-β1 expression in NRK-52E cell cultures. Overexpression of miR-29c significantly inhibits NRK-52E culture proliferation mediated by TGF-β1. miR-29c inhibited the expression of Col-1 and decreased PI3K/Akt phosphorylation. These findings revealed a novel mechanism by which miR29c inhibits the proliferation of renal interstitial fibrotic cultures by downregulating the PI3k-Akt pathway, which is controlled by TGF-β1.